Meningkatkan Minat Baca Kelas 1 SDN Trasan 4 Menggunakan Model Pembelajaran Picture and Picture - Insira, Attalla Cikha (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to improve students' interest in reading in elementary school grade 1 atSDN Trasan 4 through a learning model. Involving students directly with a total of 10students consisting of 6 male students and 4 female students. The research method usedis Classroom Action Research (CAR) which consists of three cycles where each cycle hasstages of planning, action, observation, and reflection. This research consisted of 3 cyclesand went through 4 stages, namely, planning, implementation, observation, and reflection.Efforts to increase the reading interest of elementary school students are a sharedresponsibility, between the students themselves, teachers and parents. The study showedan increase in students' reading ability in grade 1 students at SDN Trasan 4 after theimplementation of the Picture and Picture learning model with the average score ofstudents in the first cycle reaching 70.71 with 65.28% completeness and the average scorein the second cycle increasing. by reaching 80.00 with a completeness of 89.25%, then inthe third cycle it increased with an average value of 95.00 with a completeness of 97.15%.Based on the evaluation results in each lesson, the reading ability of grade 1 students atSDN Trasan 4 has increased with the Picture and Picture learning model.